EVALUASI USER INTERFACE DAN USER EXPERIENCE PADA APLIKASI DESKTOP E-SPT MENGGUNAKAN METODE HEURISTIC EVALUATION - Siahaan, Habelius Ronny Kristagus; Fahrobby Adnan; Anang Andrianto (PPM Sdirjianbang Akademi Militer, 2023)
SPT stands for notification letter. In the context of taxation in Indonesia, SPT refers to a notification letter that must be submitted by taxpayers to the tax authority to report income, tax payments, and other information required for tax purposes. The e-SPT Desktop Application was released by the Directorate General of Taxes with the main purpose of processing taxpayer tax return data submitted electronically. Users of the e-SPT application are all users who have taxpayers, especially MSMEs (Micro, Small and Medium Enterprises) with a total of 9266 users. In using this system, there are several processes, namely compiling reports, then creating .csv files, and uploading them via e-filling. Based on the results of pre-research interviews with several people who work in the field of MSMEs in Pekanbaru, there are several problems in this application that tend to lead to User Interface, such as inconsistent, indistinct, and outdated colors for backgrounds, menu bars, and other elements, and there are also problems that lead to User Experience, such as naming features and usability flow on features that confuse users. Therefore, Heuristic Evaluation is used to identify user interface usability problems and can be used for redesign with 10 more focused principles. This research uses the Heuristic Evaluation method with quantitative data analysis. The preparation of instruments developed based on each Heuristic Evaluation variable and the weighting of the questionnaire based on the severity ratings scale. The sample used in the study amounted to 383 respondents with the sampling technique using simple random sampling technique. Data collected through online questionnaires. After the data is collected, data analysis can be carried out by calculating the severity ratings value from the average of each instrument or item from each Heuristic Evaluation variable.